Strategi Peningkatan Kualitas Pelayanan Di Simalu Kopi Menggunakan Metode Quality Function Deployment (Qfd) - Bawazier, Chazqa; Hartiati, Amna; Yuarini , Dewa Ayu Anom (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Simalu Kopi is a coffee shop that offers a homey coffee-drinking atmosphere close to nature and located in the middle of Batubulan Village, Sukawati District, Gianyar Regency, Bali Province. Simalu Kopi's income is fluctuating, but from August to December 2024, there was a 30% decrease in income per month and an average of 7 complaints per month from consumers regarding the shop's service. The objectives of this study are to identify the service attributes valued by customers at Simalu Kopi, analyze the level of importance and customer satisfaction with service quality at Simalu Kopi, and develop appropriate strategies for improving service quality at Simalu Kopi. This study employs the Quality Function Deployment (QFD) method, which involves developing products or services based on consumer needs. The variables used are Wi-Fi network reliability, availability of toilet facilities, comfortable seating, ample parking space, cleanliness of the premises, tidiness of the premises, cleanliness of dining utensils, cleanliness of drinking utensils, employee appearance, strategic location, service speed, order accuracy, payment ease, issue resolution, menu mastery, safety assurance, customer trust, employee friendliness, employee sensitivity, and service dedication. The analysis revealed that the service attribute of safety assurance has the highest consumer importance value, while the service attribute of employee friendliness has the highest consumer satisfaction value. The recommended strategies for improving service quality at Simalu Kopi include providing parking area markers, using the best Wi-Fi router and regularly monitoring the network, optimizing digital and physical promotions, conducting regular briefings, evaluations, and employee soft skills training, implementing a reward–punishment system, adopting service excellence practices, and adding large-screen facilities.